2018
DOI: 10.18203/2394-6040.ijcmph20185237
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study on assessment of epidemiological factors associated with open field defecation in a tribal community

Abstract: Background: Almost 2.5 billion people don’t have the access to clean toilet globally. In 2011 sanitation coverage globally was 64%. While open defecation is declining across the globe, 15% (one billion) of the global population still defecate outdoors. OFD practices are associated with transmission of variety of infectious diseases. This study was conducted to understand the nature of defecation practices with respect to hygiene in a tribal community.Methods: It was a cross sectional study conducted among pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This finding is similar to the study done by Chakkarwar et al where 40% do not use toilet due to inadequacy of water. 11 It was also found that through most (92.8%) of them realise that toilet is necessary. They were feeling it uncomfortable (48%) to keep the toilet inside their house.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is similar to the study done by Chakkarwar et al where 40% do not use toilet due to inadequacy of water. 11 It was also found that through most (92.8%) of them realise that toilet is necessary. They were feeling it uncomfortable (48%) to keep the toilet inside their house.…”
Section: Discussionmentioning
confidence: 97%